Women’s Experiences of Sexual Harassment in Makassar’s Public Transport System - Wulandari, Niken; Syam, Febrianto (Political Sciences Program Study, 2026)
Public transportation is expected to function as a safe and inclusive space for all citizens; however, for many women, it frequently becomes a setting marked by insecurity and fear. This study examines the forms of sexual harassment experienced by female users of public transportation in Makassar City and analyzes the social, cultural, and structural factors that shape its occurrence. Using a qualitative descriptive design, data were collected through in-depth interviews with women who regularly use pete-pete, pedicabs, and Teman Bus. Thematic analysis was employed to identify recurring patterns and meanings. The findings show that sexual harassment manifests in verbal, non-verbal, and physical forms, with pete-pete emerging as the most common site. The problem is rooted not only in individual behavior but also in entrenched patriarchal norms and the cultural value of siri’, which tends to silence women, as well as structural shortcomings in transport governance that lacks gender sensitivity. Weak reporting mechanisms further limit women’s ability to seek protection and justice. The study concludes that sexual harassment in public transportation emerges from the interplay between culture, power relations, and institutional structures. It calls for gender-responsive transport policies that integrate safety measures, public education, and victim-centered reporting systems to ensure women’s rights to safe and equitable mobility.